DEVELOPMENT OF ANDROID-BASED PROTADROID APPLICATION IN PRONUNCIATION PRACTICE LEARNING FOR UNDERGRADUATE STUDENTS - Ayu Bandu Retnomurti; Nurmala Hendrawaty; Leni Tiwiyanti (University of Kuningan, 2019)
The research aims at describing the development of PROTADROID, an Android Table Program, to assist learners’ pronunciation practice by using non-native English speakers and investigating the affective aspects of using the PROTADROID. The method used was Research and Development (R&D) which has been chosen to produce a product and test the affective aspects of the product. In order to find out the affective aspect, a questionnaire was applied as an instrument in the data collection. Thirty participants were randomly selected from two Pronunciation Practice classes at Universitas Indraprasta PGRI Jakarta. Based on the development phases, PROTADROID is valid and practical. Further, the four affective aspects indicate that satisfaction is 88.2% (very satisfied), interest is 93% (very interested), attention is 76% (positive), and involvement is 85% (positive). Hence, it can be concluded that students generally understand and are capable of operating PROTADROID application with high interest.